SISTEM PENDUKUNG KEPUTUSAN PEMILIHAN CALON TEAM LEADER CLEANING SERVICE PADA PT. PPBM DENGAN METODE AHP - Arief Fadilah; Imam Himawan; Rosdiana Rosdiana (Jurnal Teknologi Informasi, 2025)
In the processing of a company or business, the right management will analyze the company's performance. In addition to assessing the company's performance, the company's management also assesses the performance of the company's employees. PT. Perdana Prima Bhakti Mandiri still uses Microsoft Excel by calculating values for each criterion manually, that is, without using the available formula functions. Then the results of the assessment are printed in sheet form. The current employee performance appraisal procedure is considered inappropriate for recruiting Team Leader candidates. Employee performance appraisal procedures have so far had little impact on employee performance, and companies analyze employee performance subjectively, resulting in inaccurate calculations. Not infrequently appointments are made based on seniority alone. This study aims to facilitate companies in selecting prospective Team Leaders using the Analytic Hierarchy Process (AHP) method with the aim of increasing the accuracy in evaluating prospective Team Leaders so that the hiring process can run smoothly.KeyWords: Decision Support System, AHP, Employee performance